2017
DOI: 10.1001/jamaneurol.2017.2136
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Pioglitazone Hydrochloride Therapy After Stroke or Transient Ischemic Attack According to Pretreatment Risk for Stroke or Myocardial Infarction

Abstract: IMPORTANCE There is growing recognition that patients may respond differently to therapy and that the average treatment effect from a clinical trial may not apply equally to all candidates for a therapy.OBJECTIVE To determine whether, among patients with an ischemic stroke or transient ischemic attack and insulin resistance, those at higher risk for future stroke or myocardial infarction (MI) derive more benefit from the insulin-sensitizing drug pioglitazone hydrochloride compared with patients at lower risk.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 35 publications
0
23
0
1
Order By: Relevance
“…Another meta-analysis investigating the effect of pioglitazone on risk of CVD events showed a benefit with pioglitazone in both patients with prediabetes (or insulin resistance) and those with T2DM [121]. Recent evidence also showed that pioglitazone decreased risk of stroke or myocardial infarction in patients without T2DM but with insulin resistance after previous stroke or transient ischaemic attack [122,123]. A large umbrella review recently confirmed that pioglitazone significantly decreased risk of major CVD events but increased risk of heart failure [124].…”
Section: Pioglitazonementioning
confidence: 99%
“…Another meta-analysis investigating the effect of pioglitazone on risk of CVD events showed a benefit with pioglitazone in both patients with prediabetes (or insulin resistance) and those with T2DM [121]. Recent evidence also showed that pioglitazone decreased risk of stroke or myocardial infarction in patients without T2DM but with insulin resistance after previous stroke or transient ischaemic attack [122,123]. A large umbrella review recently confirmed that pioglitazone significantly decreased risk of major CVD events but increased risk of heart failure [124].…”
Section: Pioglitazonementioning
confidence: 99%
“…It is also important to examine whether treatment related harms vary across risk strata because the treatment burden might not be constant across strata defined by outcome risk. When the two dimensions of risk are highly correlated (when high risk patients are also at greatest risk of treatment related harms), it becomes more difficult to segregate treatment favorable patients from treatment unfavorable ones 99100. Thus, to facilitate the interpretation of benefit-harm trade-offs, important treatment related harms should be reported at the same level of disaggregation (that is, in each of the risk strata) as the primary outcome.…”
Section: Predictive Approaches To Heterogeneous Treatment Effectsmentioning
confidence: 99%
“…Rather, initiating DBCD management at earlier Stage 1 DBCD Insulin Resistance or Stage 2 DBCD Prediabetes can more effectively reduce disease progression, symptom burden, unhealthy population metrics, and overall health care costs. In fact, there is considerable scientific evidence that validate earlier intervention in high-risk individuals, including prediabetes, to reduce CVD (177)(178)(179)(180). This new paradigm brings into focus health policy, the built environment, lifestyle medicine, and a philosophical position to restrain overmedicalization.…”
Section: Dysglycemia-based Chronic Disease-a New Multimorbidity T2d Mmentioning
confidence: 99%